Faktor-faktor yang mempengaruhi indeks prestasi mahasiswa fakultas ekonomi dan bisnis universitas tanjungpura yang bekerja paruh waktu - B01112013, Achmad Ridwan (Jurnal Pembangunan dan Pemerataan, 2017)
ABSTRACT Â  This study aims to examine and analyze the factors that affect student achievement index Faculty of Economics and Business, University of Tanjongpura working part-time (Case Study student of Economics Faculty of Economics, University Tanjongpura). With the independent variable (X) wages (WAGE), long hours of work (LJK), age (AGE) while being the dependent variable (Y) is a cumulative index of student achievement (GPA). This research is a quantitative regressive, more in particular is comparative research. Instruments of data collection using questionnaires, interviews, and documentation. Data analysis techniques in this study using multiple linear analysis techniques. The samples used in this study were 80 respondents. Results of testing the hypothesis in this study indicates that the variable WAGE significant negative effect on the index of student achievement. LJK negative effect and no significant effect on student achievement index. AGE negative effect and no significant effect on student achievement index. Â  Keyword: Part Time Work, Student Achievement Index, Wages, Hours of Work and Old Age.